SOIL FACIES – A GEOGRAPHIC LOCAL-REGIONAL COMPLETING OF SOIL TAXONOMIC UNITS - NICOLAE FLOREA (Revue Roumaine de Géographie)
Because the soil units have a double nature, genetic and geographic (“double identity”), not completely reflected by the system of soiltaxonomy, it was proposed to complete the name of the soil taxa by some additional aspects, named regional and local soil facies. These soil facies refer to the soil differentiating features of regional and respectively local significance. The soil name according to the soil taxonomy will be completed with the names of regional andlocal soil facies, generally geographic terms; for example Făgăraş skeletal loamy sand, Carpathian, Leptic-Entic Podzol. Of course, the system of soil facies entities, the criteria of differentiation and terminology of the delineated units needs to be discussed and to be agreed on. The European taxonomies could also be completed in this way with specific moisture and temperature regimes and other site characteristics. This particularization of the soil entities using soil facies can be carried on to the individualization of each soil area (delineation) in the framework of an information system and database correlated with the cadastral survey.